ESTABLISHING COMMUNICATION NETWORK MANAGEMENT AMONG THE ISLAMIC UNIVERSITY LIBRARY IN WEST JAVA - Yunus Winoto (Metakom, 2018)
Through the provision of information resources, both printed materials and electronic forms are expected to meet the needs of the academic community of the institution, so that the role of the college library as